Tracing the kelp highway hypothesis in South America: poleward shifts in kelp past distribution and archaeological evidence of human use - Gonzalez-Aragon, Daniel; Flores, Carola; Torres, Felipe I.; Broitman, Bernardo R. (Frontiers in Ecology and Evolution, 2026)
Kelp forests are among the most productive and resilient coastal ecosystems, providing long-term ecological stability and diverse resources for marine and human communities. These attributes underpin the Kelp Highway Hypothesis (KHH), which proposes that kelp-dominated seascapes facilitated early human coastal dispersal and settlement along the Pacific Rim. While most KHH research has focused on the North Pacific, its southern extension remains poorly understood. Here, we apply species distribution models (SDMs) to reconstruct the potential distribution of major kelp species along the Pacific coast of South America during three key paleoclimatic periods: the Last Glacial Maximum, the Mid-Holocene, and the Medieval Warm Period. Our results reveal persistent and spatially continuous kelp habitats over millennial timescales, with evidence of poleward shifts in suitable areas following postglacial warming. When compared with published archaeological data, these reconstructions show recurrent spatial overlap between favorable kelp habitats and early coastal sites. Although direct evidence of kelp use remains scarce, this spatial congruence supports the idea that kelp forests may have provided stable and productive environments that facilitated human occupation and mobility along the southeastern Pacific coast. By integrating paleoenvironmental modeling with archaeological evidence, this study contributes a novel South American perspective to the KHH and demonstrates the potential of SDMs for reconstructing ancient coastal ecosystems within a paleoecological framework.